Continuous Improvement From A Software Engineering Perspective: An Interview Study - Lagergren, Johannes; Nappo Andersson, Nicolas (My University, 2024)
Historically, the philosophy of continuous improvement has been widely recognised in both research and global organisations. The philosophy is commonly defined by a subset of principles and practices where any initiative taken ought to strive towards improving parts of an organisation. Subsequently, the philosophy has garnered attention in the software development field. However, the rate at which software companies have expanded throughout the last decades has made it increasingly harder to understand how continuous improvement should fundamentally be implemented. Furthermore, the current research available encompassing the philosophy appears to lack associations towards the software industry. Fortunately, human behaviour in the context of software development has attracted increased attention in the research field. Consequently, this resulted in a multidisciplinary research field that explores the interplay between human behaviour and software development processes and practices, titled Behavioral Software Engineering. With an increase in research continuously published, similarities between the two research fields are emerging, without necessarily intercorrelating. As a result, this Master’s thesis aims to explore how continuous improvement should fundamentally be implemented in software development by exploring the published literature in contrast to each other. A systematic literature review was conducted for each research field and, subsequently, the findings were then incorporated into our qualitative research methodology. The qualitative research method was conducted as part of an interview study at Polestar Performance AB, Gothenburg. In total, 9 interviews were conducted with software engineers working across diverse departments of the company. Furthermore, a thematic data analysis was performed on the data gathered. The findings derived from the qualitative research method were later compared to those derived from the systematic literature review. The findings strongly indicate that CI can be efficiently implemented in the field of SWD by emphasising particular key factors. In total, 10 fundamental key factors, shared across the two research fields, were identified as particularly critical to the successful implementation of CI. Furthermore, while CI is not directly addressed in existing BSE literature, the findings suggest that the two principles are highly compatible and that the identified factors serve as a sufficient initial step for organisations aiming to achieve CI in SWD. Lastly, findings derived from the TDA not only reinforced the considerable key factors but also provided new perspectives, not evident in the existing published literature. Ultimately, the successful implementation of CI in SWD is not only theoretically possible but highly achievable if organisations are committed to recognising these key factors and continually striving towards them.
Keywords: continuous improvement, software engineering, behavioral software engineering, systematic literature review, thematic data analysis.